PENGARUH BAHAN PENGAWETAN PHOXIM TERHADAP SIFAT PAPAN PARTIKEL KAYU KARET (hevea brasiliensis) (effect of phoxim preservation on the properties of rubber wood particleboard (hevea brasiliensis)) - Rodjak Memed; I M Sulastiningsih; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1993)
The objectives of the study was to determine the effect of phoxim on the properties of rubber wood particleboard (Hevea brasiliensis ) phoxim concentration used were 0.05,1, 1.5 and 2 % based on particle dry weight.The result showed, that the addition of phoxim preservative to particleboard reduced the values of modulus of rupture, modulus of elasticity, internal bond strength and shear strength, but increased the thicknees swelling and water absorption of particleboard. However, the phyrical. and mechanical properties of particleboard treated With phoxim preservative up to 2 % met the FAO standard for medium density particleboard and met JIS for type 150 particleboard. Compared with Indonesian standard all particleboards produced met the standard requirements except for internal bond strength.